Marketing Financial Services - Moschis G.P. (2023)
The face of the mature market for financial services has been changing. Because of the increase in life expectancy, today’s consumers at retirement age are likely to have different needs for financial services than previous generations. When it comes to marketing financial services to older adults, financial service providers should be cognizant of the diversity of older consumer needs, although their needs for convenience and personal relationships with financial vendors’ representatives are of outmost importance regardless of type of service or vendor. The importance of providing a diversity of traditional and nontraditional financial services along with membership and loyalty programs is also highlighted as gateways to cross-selling more profitable services. In order to capitalize on developments that affect the market for financial services as they relate to the aging population, financial marketers need information about the needs, preferences and habits of older Americans as they apply to financial services. This chapter presents research on older consumers’ attitudes and habits with regard to financial products and services. Based on this information, as well as information presented in the first four chapters of this book, marketing strategies are suggested for efficient and effectual delivery of financial services to satisfy older consumers financial needs and help promote their long-term well-being.